Aerobics approach in Teaching Social Dance - Yashier, T. Hadji Kasan; Bandraz, D. Sugador (Physical Education Theory and Methodology, 2023)
Study purpose.The aim of this study was to find out the performance, acceptability and effectiveness of teaching social dance using an aerobics approach among students. Materials and methods. In this study, quantitative research with a descriptive-evaluative and experimental research design (ERD) was used to determine the level of dance of cha-cha and samba social dances by two groups of participants (control and experimental groups). The researcher used a total enumeration of fourth-year and third-year students taking the Bachelor in Secondary Education major in MAPEH, using traditional and aerobics approaches. The aerobics approach was used to teach the experimental group, which included nonstop disco music in cha-cha-cha and samba as well as warm-up and cool-down exercises. The same social dance was taught to the control group, which used the traditional method of counting 8 sets of beats: 1, 2, 3, 4, 5, 6, 7, 8, 6, 5, 4, 3, 2, 1. Both the traditional and aerobic approaches were taught for 40 minutes each. Results. The findings reveal significant differences in dance performance, acceptability, and effectiveness between the control group using a traditional approach and the experimental group using an aerobics approach. Conclusions. Aerobics is recommended in teaching social dance to facilitate better learning because it allows students to learn at their own pace and according to their own interests and needs.